Alternative Method of Calculation of Pile Bearing Capacity Using Graphical Correction N-SPT - Akhmad Marzuki; Ahmad Norhadi; Rezqa Annisa (PT FORMOSA CENDEKIA GLOBAL, 2023)
Field N-SPT, used as the primary data in calculating pile bearing capacity, must be corrected by analytical methods to become N-SPT analytical correction. The analytical process requires unit weight, groundwater level, soil classification, and drilling equipment specifications to calculate field N-SPT to become analytical correction of N-SPT. A graphical approach is proposed to simplify the analytical method and to accelerate calculating the estimated pile-bearing capacity, which can be directly obtained from the relationship between the field N-SPT and the graphical correction N-SPT. The calculation results of analytically corrected N-SPT and graphical corrected N-SPT based on the field N-SPT show that the graphic of N-SPT increases linearly acording value of the field N-SPT. From all the calculations of the corrected N-SPT and pile bearing capacity obtained the ratio of pile capacity (RQ) of the graphical corrected N-SPT to the analytically corrected N-SPT are RQu = 0.93, RQp = 0.94, and RQs = 0,94. This shows that the N-SPT Graphical Correction chart can be used to simplify and accelerate the prediction of pile-bearing capacity based on field N-SPT